Self-Sacrifice in a Distressful and Threatening Environment: The Consequences of the COVID-19 Crisis in Intensifying Workplace Violence - Ebrahimi Rigi, Zahra; Mangolian Shahrbabaki, Parvin; Ahmadi, Fazlollah; Ravari, Ali (Frontiers in Psychiatry, 2022)
Background: The stress and mental pressure resulting from the challenges posed by the COVID-19 crisis exacerbated occupational stressors such as workplace violence against nurses even though nurses were endangering their lives to provide high-quality care and reduce patients' suffering. Therefore, the present study aimed to explain Iranian nurses' experiences of workplace violence during the COVID-19 crisis. Materials and Methods: This study was conducted using a qualitative approach. Twenty-five semi-structured interviews were conducted with nurses who had experienced workplace violence at COVID-19 referral centers in Kerman during the COVID-19 crisis. Conventional content analysis was used to analyze the data, and the research was reported via the COREQ checklist. Results: Analysis of the findings led to one main category, "nurses' self-sacrifice in a distressful and threatening environment," and four subcategories, which included "omitting entertainment and fun activities," "having challenging duties in unsafe conditions," "receiving insufficient support," and "nurses' toleration of disrespect." Conclusions: Crises can exacerbate workplace violence towards nurses. Thus, it is necessary to design educational programs and prevention strategies to manage the destructive psychological and occupational impact of the crises on nurses. Nurses should receive training in crisis management to cope with the intensified aggressive behavior of managers, colleagues, patients, and patient companions during the crisis. Policy-makers must be prepared to deal with crises, and they should take measures to improve nurses' mental health and quality of care.